HAK CIPTA DALAM DESAIN KOMUNIKASI VISUAL - Novi Mayasari (Ars: Jurnal Seni Rupa dan Desain, 2008)
Copy Right is one o f the Intellectual Properti/ Right instruments to protect the creations resultedfrom the field o f knowledge, art mid literary. A> a brunch o f art, Visual Communication Design is alsosheltered by the Copy Right. The protection covers the right to announce the zoork (il ntay be the right topublish or to perform the works) and the right to copy the works. The right to announce cat: be in the formo f airing, performing, exhibiting, selling, etc. The right to copy include* the copying by photocopier andscanner machine.Copy Right guarantees a visual communication designer's economic and moral rights. Theeconomic right is the economic advantage the creator gels from his creation such as the selling and theroyalty results> whereas the moral right is the right to protect the creators' good name.Keywords: copy right, law protection, Intellectual Rights